Old English Power Structure in the Warlike Nature in Riddles no. 3, no, 29, no. 50 from the Exeter Book - Herditya Wahyu Widodo (Universitas Negeri Malang, 2021)
Abstract: This study focuses on Old English nature-themed riddle texts from the Exeter Book, analyzing the natural imageries that are significant in investigating how the literary content of Old English riddles, as accepted forms of poetry, reveals the Anglo-Saxon culture of their original authors. I focus on the power structure in Anglo-Saxon society revealed in the riddles, by analyzing the topic of warlike nature in them, focusing on the riddles no. 3, “Storm”, no. 29 “Sun and Moon,” and no. 50, “Fire.” Natural experience described in these riddles is rendered by the Anglo-Saxons to reflect power hierarchy between male and female, servant and master, and human with God. The Anglo-Saxon riddles identify and assign the potent warlike attributes and actions of nature, and assign them to the more powerful factions (God, Master, Male) over the weaker factions (Humans, Servants, Female). This is done by the authors as an acceptable cultural interpretation of these natural phenomena, put in the riddles to make it possible for the riddles’ intended Anglo-Saxon audience as clues to arrive at a culturally agreeable answer. Keywords: old English, old English riddles, natural imagery, old English poetry, war imagery Abstrak: Studi ini berfokus pada teks teka-teki (Riddles) Inggris Kuno (Old English) bertema alam dari the Exeter Book, dengan menganalisa imaji alam yang signifikan, untuk mengetahui bagaimana teka-teki Inggris Kuno, sebagai salah satu karya sastra berbentuk puisi, mengungkapkan budaya Anglo-Saxon dari penulis aslinya. Saya berfokus pada struktur kekuasaan (power structure) dalam masyarakat Anglo-Saxon yang terungkap dalam teks teka-teki, dengan menganalisis topik sifat suka perang di pada teka-teki no. 3,